Metareference in Videogames - Theresa Krampe (Routledge, 2025)
Taking an original, in-depth approach, this book investigates the forms and functions of metareference in videogames.Drawing on a rich body of research in game studies, transmedial narratology, and neighbouring disciplines, the author combines detailed close-reading-style analyses of the indie games What Remains of Edith Finch, The Magic Circle and OneShot with a breadth of examples and systematic analyses that span multiple genres as well as several decades of videogaming. In doing so, the book maps different metareferential elements that can be found in videogames and proposes an original model for their analysis, while showcasing the complex interrelations among different metareferential elements in contemporary videogames. This book will appeal to videogame researchers and transmedial narratologists as well as to those interested in metaization in media and popular culture across disciplines.